Are Technical and Timing Components in Para-Badminton Classifications Different? - Aline Miranda Strapasson; Mário Antônio de Moura Simim; João Guilherme Cren Chiminazzo; Thiago José Leonardi; Roberto Rodrigues Paes (International Journal of Racket Sports Science, 2021)
Considering the reduced amount of studies with Para-Badminton (PBd) and the need to understand the technical, tactical and functional classes, the purpose of this research is to investigate the frequency of technical components and timing characteristics in categories WH1(Wheelchair/severe impairment) and WH2 (Wheelchair/minor impairment) of PBd, in addition to comparing said data between classes. Twenty PBd matches were analyzed in the men's individual category, at the 11th World PBd Championship. The mean playing time of the matches was 1780 seconds (SD = 575) for the WH1 class and 2012 seconds (SD = 1098) for WH2. The average rally time was 10.2 minutes (SD = 8.4) for the WH1 and 12.5 (SD = 12.5) for WH2. The average related to pause time was 15 seconds (SD = 10.3) for the WH1 class and 14.1 (SD = 10.5) for the WH2. The mean number of shots in the shuttle per game obtained was 552 (SD = 197) and 719 (SD = 480) for class WH1 and WH2, respectively. In both classes: the most frequent shots performed by the players were Clear, Lob, Drop, and Net-shot; the players used backhand more often than the forehand service and the short service compared to the long one; the errors stood out in relation to the winner points. In addition to this, there was a higher proportion of shots at the front of the court in both classes. It was found that the WH2 class showed a higher intensity (longer rally time and shorter pause time) and a higher frequency of technical actions (higher number of hits on the shuttle) when compared to the WH1. This information can assist coaches during training to guide the development of the temporal and technical aspects of the PBd, as well as monitor them during matches to obtain victory.